Penentuan Indikator Kualitas Tanah dari Reklamasi Bekas Tambang - Inun Setyani; M. Arief Budihardjo; Fuad Muhammad (Seminar Nasional Lahan Suboptimal, 2020)
Setyani I, Budihardjo MA, Muhammad F.  2020. The determination of soil quality indicators from ex-mining reclamation. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Soil plays a role in maintaining and improving environmental quality. As a result of mining activities, the soil quality will decline. There are six key indicators to determine the recommended soil quality, namely soil organic matter content, soil acidity, soil bulk density, available water capacity, soil aggregation and respiration. There is also a need for a policy regarding reclamation as a form of controlling ex-mining land. Reclamation is a soil management activity which includes improving the physical condition of the soil, constructing reservoirs to improve the quality of mine water, and revegetation activities. Reclamation activities must be carried out in an effort to reduce environmental damage and divert the function of ex-mining land into agricultural land. This paper aims to explain the determination of soil quality indicators and the factors that support the success of ex-mining land reclamation. With the success of reclamation carried out on ex-mining land, it is hoped that environmental sustainability and agricultural sustainability can be maintained to support food security.